Improving Students’ Learning With NHT Model of Teaching In Natural Science Courses - Indah Pratiwi (International Journal of Trends in Mathematics Education Research, 2019)
The Numbered Heads Together (NHT) model of learning enables students to grasp the purpose behind the teacher’s instruction in order for the students to become motivated to learn from the teacher. The subjects in this study were students from class A, a total of 28 students. Each of the conducted studies involved planning, implementation, observation and reflection stages. Data collection was performed using both observation and tests. According to the results of the initial test (pre-test)-before the action-the grade average was 56.4 with the level of students’ learning outcomes as many as 7 students (25%) still scoring very low, but the action-incorporating the Numbered Heads Together (NHT) learning model by the teacher in the first cycle-led to some improvement. Improved learning outcomes obtained following the first cycle, with the class average score being 62.3, indicating that the level of mastery under standard instruction amounted to as many as 13 students (46.4%) still classified as moderate, whereas students’ activities or actions based on observations made by peers were relatively low at 60.5%. As the aforementioned increase did not reach the set standard values, efforts needed to be made to improve and develop during the second cycle. Following the second cycle, the post-test revealed further improvement in the average grade value, which increased to 70.4, and the level of students’ learning outcomes under standard instruction with as many as 19 students (67.9%) belonging to the good category; the standard instruction underwent changes in learning and students’ actions or activities were classified as good, reaching as high as 80.3.